POSTOPERATIVE MANAGEMENT OF PATIENTS AFTER BARIATRIC SURGERY - Jumaev N.A., Teshaev O.R., Kurbanov G.I., Juraev J.Z., Lim I.I., Lekomseva M.J. (Central Asian Journal of Medicine, 2025)
Bariatric surgery represents the most effective treatment for morbid obesity, with long-term success heavily dependent on comprehensive postoperative care. This review examines evidence-based approaches to postoperative management, including nutritional support, vitamin supplementation, physical rehabilitation, and long-term follow-up protocols. Understanding the complexities of postoperative care is crucial for optimizing patient outcomes and preventing complications.